Brazilian co-authorship overseas: the Journal of Post Keynesian Economics and related journals - Matteucci de Andrade Lopes, Caio; de Lacerda Antunes Borges Lopes, Renata (Brazilian Keynesian Review, 2020)
The purpose of this article is to evaluate the importance of post-Keynesianism ideas for international scientific production of Brazilian researchers. The methodology employed uses an econometric technique in order to analyze the Brazilian participation in nine scientific journals in the course of twenty years: 1997-2016. The probability of a Brazilian co-author being greater for The Journal of Post Keynesian Economics (hereinafter JPKE) - in relation to the other journals - was evaluated by means of a logit, in which the dependent variable assumes value one when at least one co-author of the given article is Brazilian and zero otherwise. The results show that the probability of Brazilian co-authorship is greater for heterodox journals, especially JPKE.